Alpha antiadrenergic effect of Achyrocline bogotensis extract (“Vira Vira”) in isolated rat aortic ring - LARA, Nidya; RINCÓN, Javier; GUERRERO, Mario F. (Vitae, 2017)
Background: The treatment of symptoms of prostatic hyperplasia is among the traditional uses of Achyrocline bogotensis (Kunth) [N.V. “Vira Vira”, Compositae] in Colombia. Pharmacological therapy for this disorder depends mainly on alpha-1 antiadrenergic agents, and the mechanism has not been studied previously using A. bogotensis. Objectives: To assess the alpha-1 antiadrenergic effect of the extract obtained from the aerial parts of A. bogotensis in isolated aortic rings from Wistar rats. Methods: The study compared the effects of the ethanol extract of A. bogotensis, prazosin (reference) and DMSO (control) in rings stimulated with phenylephrine (PE) or KCl. The capacity to reduce the PE pressor effect by the ethanol extract (pD2’ value) was determined. To quantify the A. bogotensis relaxant potency, increasing concentrations of the ethanol extract (0.1 µg/mL-0.1 mg/mL), were added cumulatively to isolated aortic rings pre-contracted with PE (0.1 µM) or KCl (80 mM). To explore the possible participation of nitric oxide (NO), L-NAME (100 µM) was administered to aortic rings exposed to cumulatively increasing concentrations of PE in isolated aortic rings in the presence of the extract (10 µg/mL). Aqueous, butanol and dichloromethane fractions (10 µg/mL) obtained from the ethanol extract were assayed. Phytochemical screening was also performed. Results: Prazosin and A. bogotensis extract notably reduced the contraction induced by PE whereas their inhibitory effect in rings contracted with KCl were lower. A. bogotensis ethanol extract showed a high capacity for reducing the PE pressor response (pD´2 : 5.51) as well as total efficacy for relaxing rings previously precontracted with PE. The relaxant efficacy and potency of A. bogotensis extract against rings previously contracted with KCl were notably lower. L-NAME partly reverted the inhibitory effect of A. bogotensis. Aqueous, butanol and dichloromethane fractions gave inhibitory responses lower than that obtained with the ethanol extract. Phytochemical screening of A. bogotensis extract revealed the significant presence of flavonoid and triterpene metabolites. Conclusions: These results suggest that A. bogotensis elicits a smooth muscle relaxant effect related to the alpha-1 antiadrenergic mechanism. This response is partially NO dependent and seems to be due to interactions among active metabolites likely to be of flavonoid and/or terpenoid nature.